2017
DOI: 10.1016/j.radonc.2016.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Does an integrated boost increase acute toxicity in prone hypofractionated breast irradiation? A randomized controlled trial

Abstract: SummaryThis is the first randomized trial reporting on the 2-year cosmetic outcome of prone and supine whole-breast irradiation in 94 patients with a cup size of at least C. Better cosmetic outcome was observed in prone-treated patients after 2 years with less skin color changes (PZ.05), less edema (PZ.06), and less worsening of cosmesis assessed by the Breast Cancer Conservation Treatment.cosmetic results software on digital photographs with both arms elevated.Purpose: To report the 2-year cosmetic outcome of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
(34 reference statements)
2
17
0
Order By: Relevance
“…Many published clinical experiences with H‐SIB have been reported, 12,19‐23 but these usually have short follow‐up and few have been compared with C‐SIB. Acute toxicity of H‐SIB was mild 24‐27 and slightly lower than in HF with sequential boost (H‐SEQ), 28 C‐SIB 27,29,30 or CF with sequential boost (C‐SEQ) 26,30 . Two prospective randomized trials comparing H‐SIB vs C‐SEQ or H‐SEQ remain unpublished 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Many published clinical experiences with H‐SIB have been reported, 12,19‐23 but these usually have short follow‐up and few have been compared with C‐SIB. Acute toxicity of H‐SIB was mild 24‐27 and slightly lower than in HF with sequential boost (H‐SEQ), 28 C‐SIB 27,29,30 or CF with sequential boost (C‐SEQ) 26,30 . Two prospective randomized trials comparing H‐SIB vs C‐SEQ or H‐SEQ remain unpublished 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Local control, disease-free survival and overall survival at 3 years were similar between the two groups. There are two small randomized controlled trials studying hypofractionated whole-breast radiotherapy (HF) and comparing SIB to seqB [27,28]. Both trials showed a reduction of acute skin toxicity by the incorporation of SIB.…”
Section: Discussionmentioning
confidence: 99%
“…Both trials showed a reduction of acute skin toxicity by the incorporation of SIB. However, the overall incidence of radiation dermatitis is significantly lower with hypofractionated radiotherapy [29] and one trial used prone radiotherapy [27], which might impair the cross-trial comparison. Two retrospective studies of HF-SIB and NF-SIB have been published recently.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, other studies have reported on the acute toxicities and patient-reported outcome. One randomized controlled trial reported by Paelink et al demonstrated no increase in moist desquamation after SIB in a randomized trial of 167 patients [20]. Another randomized controlled trial compared hypofractionated radiotherapy with SIB to conventionally fractionated radiotherapy with sequential boost.…”
Section: Simultaneous Integrated Boost (Sib)mentioning
confidence: 99%